Progression of Primary Gastric Diffuse Large B-Cell Lymphoma after Helicobacter pylori Eradication - Saito, Makoto (Case Rep Gastroenterol, 2020)
In Helicobacter pylori−positive, localized primary gastric diffuse large B-cell lymphoma (DLBCL), an increasing number of reports have recently been published on the effectiveness of H. pylori eradication (HPE). However, HPE treatment strategies for gastric DLBCL, including its indications, have yet to be examined. No detailed report has been published on a case of gastric DLBCL unsuccessfully treated by HPE. A 64-year-old female and a 70-year-old male were pathologically diagnosed with chronic active gastritis and mucosa-associated lymphoid tissue lymphoma, respectively. Both patients were positive for H. pylori, so HPE was employed. The disease progressed within 1 year, and both patients were pathologically diagnosed with DLBCL by endoscopic biopsy. On reviewing the first pathology slide, both patients were diagnosed with DLBCL. That is, the 2 patients had primary gastric DLBCL; however, they exhibited progressive disease after HPE. This failure of HPE treatment may be due to the initial lymphomas being multiplex ulcerative lesions. In both cases, complete remission was achieved by chemotherapy (plus radiation therapy) without recurrence for more than 3 years.